Capital structure and firm performance: focusing on consumer products sector of Malaysian listed companies / Nadzirah Yusof - Yusof, Nadzirah (2016)
Capital structure is one of the sources of the firm which a combinations of debt and equity. Some of the firm performance being affected by the amount of the capital structure of the firm. This study is to investigate the relationship between capital structure and firm performance in consumer products sector of listed companies in Malaysia. This study measured by Return on Assets (ROA) as dependent variables, Short-term Debt (STD), Long-term Debt (LTD), Total Debt (TD) as independent variables also size of the firm (SIZE) as the control variable. This study covers one major sector of consumer products sector in Bursa Malaysia. Using panel data, 12 firms of consumer products sector were identified as the sample of this study and using 2009 to 2015 quarterly data with a total observations of 336. The study employs Random Effect Regression Model to analyse all independent and dependent variables. All test running using E-Views 7 software. From the findings, all variables are significant namely Short-Term Debt (STD), Long-term Debt (LTD), Total Debt (TD) and while size of the firm (SIZE) was not significant towards Return on Assets (ROA). There are negative relationship from alt the independent variables and control variables except for Total Debt (TD) which given positive relationship with Return on Assets (ROA).